Enhancement of waste activated sludge anaerobic digestion by a novel chemical free acid/alkaline pretreatment using electrolysis - Charles, W.; Ng, B.; Cord-Ruwisch, R.; Cheng, Liang; Ho, G.; Kayaalp, A. (I W A Publishing, 2013)
Anaerobic digestion of waste activated sludge (WAS) is relatively poor due to hydrolysis limitations. Acid and alkaline pretreatments are effective in enhancing hydrolysis leading to higher methane yields. However, chemical costs often prohibit full-scale application. In this study, 12 V two-chamber electrolysis using an anion exchange membrane alters sludge pH without chemical dosing. pH dropped from 6.9 to 2.5 in the anode chamber and increased to 10.1 in the cathode chamber within 15 h. The volatile suspended solids solubilisation of WAS was 31.1% in the anode chamber and 34.0% in the cathode chamber. As a result, dissolved chemical oxygen demand increased from 164 to 1,787 mg/L and 1,256 mg/L in the anode and cathode chambers, respectively. Remixing of sludge from the two chambers brought the pH back to 6.5, hence no chemical neutralisation was required prior to anaerobic digestion. Methane yield during anaerobic digestion at 20 d retention time was 31% higher than that of untreated sludge. An energy balance assessment indicated that the nonoptimised process could approximately recover the energy (electricity) expended in the electrolysis process. With suitable optimisation of treatment time and voltages, significant energy savings would be expected in addition to the benefit of decreased sludge volume. © IWA Publishing 2013.